Efficient Transformation of Inactive Nitriles into 5-Substituted 1H-Tetrazoles Using Microwave Irradiation and Their Applications - Yoneyama, Hiroki; Usami, Yoshihide; Komeda, Seiji; Harusawa, Shinya (Synthesis, 2013)
Efficient transformations of inactive nitriles into 5-substituted 1H-tetrazoles in DMF in a microwave reactor are described. The present method is applied to the synthesis of tetrazolato-bridged dinuclear platinum(II) complex and tetrazole C1-ribonucleoside phosphoramidite.
Keywords: tetrazole; DMF; microwave; platinum(II) complex; phosphoramidite